Curriculum policy networks: Getulio Vargas Foundation’s enactment (Práxis Educativa, 2021)
In this article, we analyze changes in the mode of governance exercised by philanthropic and private institutions in education, with a focus on the policy networks of Stephen J. Ball. The notion of networks is associated with Ernesto Laclau’s notion of social as discursive practice, making us conceive these networks as spaces of dispute in education policies and as representation of the social, but never on the whole, but productive to interpret the influence of institutions in political decisions. As example of this analysis, we focused on the protagonism of the Getulio Vargas Foundation (FGV), after the approval of the National Curriculum Common Core (Base Nacional Comum Curricular – BNCC), seeking to highlight its enactment, including international, in the “implementation” actions of the BNCC and in the constitution of “new” processes of private management of public education.Keywords: Curriculum policy. Policy networks. Getulio Vargas Foundation. National Curriculum Common Core. Discourse.